N-Hydroxy-N-methyl-ammonium chloride. - Ng, Seik Weng (International Union of Crystallography, 2008)
In the crystal structure of the title compound, CH(6)NO(+)·Cl(-), the cations and anions are linked by N-H⋯Cl and O-H⋯Cl hydrogen bonds into an undulating layer motif [Schläfli symbol: 4(8).6(8).8(2)]. All non-H atoms lie on a mirror plane.